Absence of ototoxicity of teichomycin A2 in guinea pigs. - Brummett, R E (1987)
Teichomycin A2 is a new antibiotic that is similar to vancomycin. Because vancomycin is reported to be ototoxic, teichomycin A2 was tested for ototoxicity. No evidence of ototoxicity was found. Furthermore, ethacrynic acid, a diuretic that augments the ototoxicity of many drugs, did not enhance ototoxicity with teichomycin A2.